Carbon ion radiotherapy with pencil beam scanning for hepatocellular carcinoma: Long‐term outcomes from a phase I trial. Issue 3 (15th November 2022) - Hong, Zhengshan; Zhang, Wenna; Cai, Xin; Yu, Zhan; Sun, Jiayao; Wang, Weiwei; Lin, Lienchun; Zhao, Jingfang; Cheng, Jingyi; Zhang, Guangyuan; Zhang, Qing; Jiang, Guoliang; et al.
Abstract: This study evaluates the feasibility of the pencil beam scanning technique of carbon ion radiotherapy (CIRT) in the setting of hepatocellular carcinoma (HCC) and establishes the maximum tolerated dose (MTD) calculated by the Local Effect Model version I (LEM‐I) with a dose escalation plan. The escalated relative biological effectiveness‐weighted dose levels included 55, 60, 65, and 70 Gy in 10 fractions. Active motion management techniques were employed, and several measures were applied to mitigate the interplay effect induced by a moving target. CIRT was planned with the LEM‐I‐based treatment planning system and delivered by raster scanning. Offline PET/CT imaging was used to verify the beam range. Offline adaptive replanning was performed whenever required. Twenty‐three patients with a median tumor size of 4.3 cm (range, 1.7–8.5 cm) were enrolled in the present study. The median follow‐up time was 56.1 months (range, 5.7–74.4 months). No dose limiting toxicity was observed until 70 Gy, and MTD had not been reached. No patients experienced radiation‐induced liver disease within 6 months after the completion of CIRT. The overall survival rates at 1, 3, and 5 years were 91.3%, 81.9%, and 67.1% after CIRT, respectively. The local progression‐free survival and progression‐free survival rates at 1, 3 and 5 years were 100%, 94.4%, and 94.4% and 73.6%, 59.2%, and 37.0%, respectively. The raster scanning technique could be used to treat HCC. However, caution should be exercised to mitigate the interplay effect. CIRT up to 70 Gy in 10 fractions over 2 weeks was safe and effective for HCC. Abstract : No dose‐limiting toxicity was observed in this phase I dose escalation trial, and the maximum tolerated dose had not been reached. After a median follow‐up time of 56.1 months (range, 5.7–74.4 months), we obtained excellent 5‐year survival rates (overall survival rate of 67.1% and local progression‐free survival rate of 94.4%). Our study demonstrated that the pencil beam scanning (raster scanning) technique was feasible for HCC, and carbon ion radiotherapy up to 70 Gy in 10 fractions over 2 weeks was safe and effective for HCC.